Thickness-dependent magnetotransport: from multilayer graphene to few-layer graphene. (November 2017) - Li, H.; Zeng, Y.J.; Hu, X.J.; Zhang, H.H.; Ruan, S.C.; Van Bael, M.J.; Van Haesendonck, C.
Abstract: We present a comparative study of magetoresistance (MR) behaviors in few-layer graphene (FLG) and multilayer graphene (MLG) with various thicknesses. A maximum MR as large as 9500% is observed in a ∼23 nm sample @ 2.5 K, with a non-saturating linear characteristic up to 7 T. MR decreases with increasing temperature and is proportional to the average mobility < μ > in ∼23 nm and ∼12 nm thick samples. In a thinner sample with thickness of ∼1.6 nm, the maximum MR value is only 68% @ 7 T @ 280 K, which is two orders of magnitude smaller than those in the thicker samples. We attribute the MR mechanism of the FLG to mobility fluctuations Δ μ . Both the above situations follow the classical Parish and Littlewood model. Through comparison we unveil that both changes in the band structure resulting from a different sample thickness and the disorder induced by sample preparation and graphene/substrate interface are responsible for the MR behavior in the thickness variation. Our results indicate that MR tuning can be realized by precise thickness control in multilayer graphene. Graphical abstract: Different magetoresistance behaviors are observed in multilayer ((a) and (c)) and few-layer ((b) and (d)) graphene samples. Magetoresistance controlling can be realized through tuning the sample thickness.